2019
DOI: 10.1111/pce.13511
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal responses of photosynthetic parameters in maize and sunflower and their relationship with leaf functional traits

Abstract: Estimates of seasonal variation in photosynthetic capacity (P c ) are critical for modeling the time course of carbon fluxes. Given the time-intensive nature of calculating P c parameters via gas exchange, it is appealing to calculate parameter variation via changes in chlorophyll (Chl) and nitrogen (N) content by assuming that P c scales with these variables. Although seasonal changes in P c and the relationships between N and P c have been evaluated in forest canopies, there is limited data on seasonal param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 96 publications
(177 reference statements)
0
20
0
Order By: Relevance
“…The ratio of nitrogen allocated in Rubisco to the total nitrogen in leaf varies among species (Ghimire et al, 2017). This ratio is also affected by environment (Liu et al, 2018) and has seasonal variations (Croft et al, 2017; Miner & Bauerle, 2019). Therefore, accurate modeling of Vcmax 25 requires a factor that characterizes the fraction of the photosynthetic nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of nitrogen allocated in Rubisco to the total nitrogen in leaf varies among species (Ghimire et al, 2017). This ratio is also affected by environment (Liu et al, 2018) and has seasonal variations (Croft et al, 2017; Miner & Bauerle, 2019). Therefore, accurate modeling of Vcmax 25 requires a factor that characterizes the fraction of the photosynthetic nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…For example, by mapping the distribution of leaf age throughout a crown, the whole-canopy performance may be compared among canopies comprised of different age leaves [22,23]. The challenge when modeling the time course of carbon fluxes would be to identify architectural properties that positively impact the total canopy CO 2 uptake [24].…”
Section: Discussionmentioning
confidence: 99%
“…Leaf is an important organ for plants to obtain energy, resources and nutrition, and it is also the most sensitive organ to environmental change and has strong plasticity (Franco et al, 2005;Jin et al, 2011). Leaf functional traits can objectively re ect the in uence of environmental changes on plants and the adaptability of plants to the environment, and predict the characteristics of plants and urban ecosystems (Eamus 2008;Niinemets 2015;Miner & Bauerle 2019). In this study, it was found that the functional traits of plants change regularly with the change of dust deposition.…”
Section: Effect Of Urban Atmospheric Particulate Matter On Leaf Functional Traitsmentioning
confidence: 99%